Marketing Opportunities for Blood Ark Clams and Ponderous Ark Clams - Robert L. Degner; Tiffany B. Southwell; Leslie N. Sturmer; Kimberly L. Morgan (EDIS)
The basic objective of this study was to determine the present market potential of Blood Ark and Ponderous Ark clams in the United States. This paper summarizes research that attempted to quantify the shellfish trade industry's present awareness and acceptance of the Blood Ark and Ponderous Ark clams as a first step in evaluating the economic feasibility of producing these clams in commercial quantities using commercially feasible aquacultural production techniques by the existing hard clam industry. This is EDIS document FE478, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published August 2005.